Dampak Program Pembiayaan Mikro terhadap Peningkatan Kesejahteraan Pelaku UMKM: (Studi Kasus pada Koperasi Wanita Desa Minggirsari, Kabupaten Blitar) - Dita Ayu Primantari; Wydha Mustika Maharani; Abdul Aziz Al Kaharudin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The main issue faced by MSME actors is limited capital, which hinders business development and their well-being. This study aims to evaluate the impact of the micro-financing program on improving the well-being of MSME actors, with a case study at the